Transient stability criterion of grid-forming converter based on DC voltage synchronization control considering current limit - Jingrui LIU; Zengze TU; Yufei ZHANG; Yang ZHANG; Jiapeng LI; Yujun LI (电力工程技术)
In order to address the synchronization stability of grid-forming converters considering current limiting constraints，a switching dynamic model of the system of a single converter connected to the grid based on direct current voltage synchronization control （DVSC） strategy considering current limiting is established in this paper. Grid-forming converters without current limiting constraints will only operate in the constant voltage control mode after fault clearance，while those with current limiting constraints may stabilize in different modes like constant voltage control mode or constant current control mode. Therefore，the transient stability of studied model is analyzed using the segmental equal area criteria （SEAC） in this paper and the analytical expression of the critical clearing angle （CCA） is derived，revealing the mechanism by which the saturation current angle affects the stability of the system. In addition，a setting method of current saturation angle that can enhance the transient stability margin is proposed in this paper，which not only prevents the system from being locked into the current limiting mode after fault clearance but also achieves the maximum critical clearing angle and deceleration area. Finally，simulations based on MATLAB/Simulink are carried out to verify the correctness of the expression of critical clearing angle and setting method of current saturation angle.